2014
DOI: 10.1002/jbm.a.35239
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin–siloxane nanoparticles to deliver nitric oxide for vascular cell regulation: Synthesis, cytocompatibility, and cellular responses

Abstract: Nitric oxide (NO) is an important mediator in cardiovascular system to regulate vascular tone and maintain tissue homeostasis. Its role in vascular cell regulation makes it promising to address the post-surgery restenosis problem. However, the application of NO is constrained by its high reactivity. Here, we developed a novel NO-releasing gelatin-siloxane nanoparticle (GS-NO NP) to deliver NO effectively for vascular cell regulation. Results showed that gelatin-siloxane nanoparticles (GS NPs) could be synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…NO release from S -nitroso-penicillamine-modified Ti-6Al-4V was monitored over 48 h using the Griess assay [23,37]. Briefly, three coupons of S -nitroso-penicillamine-modified Ti-6Al-4V were added to three separate vials containing 900 μL of PBS and placed on an incubator/shaker at 37 °C, while protected from light.…”
Section: Methodsmentioning
confidence: 99%
“…NO release from S -nitroso-penicillamine-modified Ti-6Al-4V was monitored over 48 h using the Griess assay [23,37]. Briefly, three coupons of S -nitroso-penicillamine-modified Ti-6Al-4V were added to three separate vials containing 900 μL of PBS and placed on an incubator/shaker at 37 °C, while protected from light.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al applied gelatin–siloxane (GS) NPs to deliver nitric oxide (NO) to vascular cells in order to regulate the vascular cell behavior and prevent restenosis. 17 , 86 Acid orange 7 (AO7) assay was applied to quantify amino groups on GS NPs. After preparing NO-releasing S-nitrosothiol (RSNO) modified GS NPs (GS-NO NPs), they were subjected to size determination.…”
Section: Nanoparticles As Atherosclerosis Prevention and Treatment Dementioning
confidence: 99%
“…The NO payload could reach 11.26 µM/mg, and the release could last for 101 h with a half-life of 253 min. Recently, Zhang et al [87] reported a cytocompatible NO-releasing NP synthesized via thiolation of gelatin-siloxane NPs. The resultant NO-releasing NPs (GS-NO NPs) could release NO following a first-order exponential profile (∼0.12 µM/mg within 7 days), and could realize rapid intracellularization within 2 h. In vitro study with human aortic SMCs and human umbilical vein ECs suggested that GS-NO NPs could exhibit a dose-dependent effect for inhibited SMCs proliferation and promoted ECs proliferation, with great potential of preventing vascular restenosis.…”
Section: Silica Particlesmentioning
confidence: 99%